Inhibition of neuronal nitric oxide synthase attenuate the hypothermic effect of ketamine-magnesium sulfate combination in rats. (May 2018) - Vujović, Katarina Savić; Vučković, Sonja; Đurović, Aleksandar; Knežević, Nebojša Nick; Prostran, Milica
Abstract: Ketamine and magnesium as NMDA receptor antagonists interact synergistically to decrease body temperature in rats. The mechanism of the hypothermic effect of the ketamine-magnesium sulfate combination has not been studied until now. The aim of this study was to examine whether nitric oxide (NO) has a role in the hypothermic effect of ketamine (10 mg/kg) and the combination of ketamine (5 mg/kg) and magnesium sulfate (5 mg/kg). The body temperature was measured by insertion of a thermometer probe 5 cm into the colon of unrestrained male Wistar rats (200–250 g). N(ω)-nitro-L -arginine methyl ester (L-NAME 2.5 and 5 mg/kg) as non-selective inhibitor of nitric oxide synthase at a dose of 5 mg/kg antagonized the effect of the ketamine-magnesium sulfate combination at 60 min (p < 0.05) and 90 min (p < 0.01). Ketamine induced hypothermia was not affected by administrating of L-NAME (2.5 and 5 mg/kg). Inhibitor of inducible nitric oxide synthase N6-(1-Iminoethyl)-L -lysine hydrochloride (L-NIL 1.25 mg/kg and 2.5 mg/kg, sc) did not significantly change the hypothermic response evoked by the ketamine-magnesium sulfate combination. Inhibitor of neuronal nitric oxide synthase N-ω-Propyl-L -arginine hydrochloride (L-NPA) at a dose of 2 mg/kg antagonized the combination at 60 min when it achieved the maximum effect. The NO pathway is not involved in the hypothermic effect of ketamine. Production of NO through neuronal NO synthase, might play a role in the mechanism of the hypothermic effect of the ketamine-magnesium sulfate combination. Highlights: Ketamine and magnesium interact synergistically to decrease body temperature. The NO pathway is not involved in the hypothermic effect of ketamine. Enhancement of neuronal NO synthase and the production of NO might play a role in the mechanism of the hypothermic effect of the ketamine-magnesium sulfate combination.